Managing Bull Fertility in Beef Cattle Herds: AN153/AN153, 2/2006 - Hansen, Gary R. (EDIS, 2019)
The purpose of this paper is to discuss how producers can evaluate and manage bull fertility within beef cattle herds. This document is AN153, one of a series of the Animal Science Department, UF/IFAS Extension. Original publication date February 2006.